Multifunctional Characteristics of Carbon Fibers Modified with Imidazolium Ionic Liquids - Bilal Ghafoor; Henri Stephan Schrekker; Sandro Campos Amico (Molecules, 2022)
A multifunctional designing approach is of great importance for advanced composite applications. This study assessed the use of ionic liquids (ILs) to modify the surface of carbon fiber (CF) and impart multifunctional characteristics to it. For that, ethanolic solutions of different ILs, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium chloride and 1-(2-hydroxyethyl)-3-methylimidazolium chloride, at different concentrations, were used to treat the CF. Fourier-transform infrared spectroscopy confirmed the presence of IL on the CF surface. The contact angle for 1% w/v IL-treated CF and DGEBA epoxy decreased by up to 35%, corresponding to an increase in surface energy of fiber, accompanied by an increase of 91% in interfacial shear strength. These enhancements were achieved with the hydroxy-functionalized IL, showing the tunability of CF properties through the N-imidazolium substituent. An increase in crystallite size along the basal plane was also found due to the ordering of the graphitic structure on the surface. Moreover, there was a decrease in electrical resistivity of 77%. In all, the imidazolium ILs were considered a promising approach to induce multifunctional characteristics, namely enhanced interfacial strength and electrical conductivity, to unsized CF, which can also be beneficial for recycled fibers without deteriorating their inherent surface properties.